Hydrogen and carbon interaction in a FeNi alloy with a vacancy - Gonzalez, Estela Andrea (2009)
The bonding of hydrogen and carbon to Fe and Ni in a 50:50 alloy is analysed using density functional calculations. The changes in the electronic structure of a L10 alloy upon C and H introduction at a vacancy region are addressed and a comparison with H or C in pure metals is drawn. H in bulk FeNi alloy with a vacancy locates at a tetrahedral site shifted towards the vacancy. Instead, C prefers an octahedral site (Fe based). The vacancy acts as strong traps of both C and H. Fe-Ni atoms are initially more strongly bonded to each other due to the vacancy formation. Consequently, the Fe-Fe, Fe-Ni and Ni-Ni bond strengths are diminished as new metal-C or metal-H bonds are formed. The most affected bond is the Fe-Ni, whose overlap population decreases by 72%. An analysis of the orbital interaction reveals that the Fe-H bonding involves mainly the Fe 4s, H 1s and Ni 4s orbitals. In the case of the sequential absorption, the C-H interaction is almost zero at a distance of 2.72 Å. The main interactions of these interstitials are developed with either Fe or Ni. We also consider the absorption sequence (H first or C first) and its influence on the electronic structure. Our results could be relevant to understand some steps of the carburization process during thermal cracking operations where hydrogen atoms are present.